Patient-specific fluid simulation of transcatheter mitral valve replacement in mitral annulus calcification - Hill, Samuel Joseph; Young, Alistair; Prendergast, Bernard; Redwood, Simon; Rajani, Ronak; De Vecchi, Adelaide (Frontiers in Cardiovascular Medicine, 2022)
To assess the interplay between these haemodynamic metrics, implanted device and patient-specific anatomy in transcatheter mitral valve replacement (TMVR), we leveraged progress in Computational Fluid Dynamics (CFD) modelling and high performance computing to create 3D computer models of the left ventricle that are patient- and device-specific based on preprocedural data. These models can be used to estimate ventricular haemodynamics after implantation, with the goal to elucidate mechanisms of LVOT obstruction and valve thrombosis and to include functional metrics in the preprocedural assessment for a comprehensive evaluation of postprocedural risks. Three patients diagnosed with severe MAC were selected for the study, all with native anatomy suitable for TMVR with a Sapien 3 bioprosthetic device. The blood pool of the LV was segmented with manual contouring at the peak systolic-frame in the multiphase CT series using segmentation software. Wall motion tracking was performed using temporally sparse free-form deformation to create a vector field of displacement values, which were then applied to the surface mesh, deforming the initial surface mesh to match the wall motion at each time frame in the CT series. From the end-systolic surface mesh a polyhedral volume mesh was created using the commercial software STAR-CCM+. A CAD model of the Sapien 3 was embedded into the fluid domain in the position of the mitral annulus prior to volumetric meshing. CFD simulations based on the patient-specific anatomy and boundary conditions were performed using STAR-CCM+, solving for the incompressible Navier-Stokes equations. The methodology presented has successfully captured the increased pressure gradient and maximum wall shear stress as a result of reduced neo-LVOT area, and also provided insight into the mechanistic interpretation of the device-induced thrombus formation that is increasingly observed in transcatheter bioprosthetic valves, showing the potential of CFD analysis to provide in the future important information on the patient-specific haemodynamics in the context of postprocedural risk assessment.